"A (tiger) king's ransom": Dark personality features predict endorsement of exotic animal exploitation. (February 2023) - O'Connor, Victoria L.; Vonk, Jennifer
Abstract: Individuals with different personality traits likely hold different attitudes about animal care and conservation and may reflect differently on exposure to media programming such as the controversial Tiger King: Murder, Mayhem, and Madness documentary. We surveyed 116 community and 473 college participants that had and had not viewed the documentary and examined the association between traits measured by the Personality Inventory for DSM-5-Brief Form and the Short Dark Triad scales and endorsement of exotic pet ownership and unaccredited zoos. Those that viewed the documentary had more negative attitudes toward exotic pet ownership and unaccredited zoos in general, but having low negative affect, low empathic concern, high antagonism, and psychopathy predicted endorsement of exotic pet ownership and unaccredited zoos regardless of whether participants viewed Tiger King. Being male and high in narcissism additionally predicted positive attitudes toward exotic animal ownership. Respondents reported feeling more positively about exotic pet ownership after viewing Tiger King if they were high in narcissism and low in empathy, supporting the hypothesis that individuals high in dark traits and individuals low in empathy may be more supportive of exploitation of exotic animals and therefore less sympathetic to issues surrounding animal welfare. Future research should further identify the role of personality in exotic pet ownership and endorsement of controversial and inhumane animal activities. Highlights: Respondents who viewed Tiger King were less likely to endorse animal exploitation. Respondents low in empathy were less likely to endorse animal exploitation. Respondents low in negative affect were more likely to endorse animal exploitation. Respondents high in psychopathy were more likely to endorse animal exploitation